Design of a motorcycle ambulance with an integrated passenger seat mechanism for emergency response - Yilmaz, Cuneyt; Livatyali, Haydar; Gur, Emre; Arslan, M. Selcuk (SAGE PUBLICATIONS LTD, 2026)
It is aimed to develop a unique method and system to effectively and immediately transport civilians injured during natural disasters, accidents, or terrorist attacks to hospitals. The development, prototyping and performance test studies of the mechanical system were performed. The system was required ensure that the patient is seated in a modular chair easily lifted and fixed to the rear of the motorcycle with a special mechanism, and that the motorcycle remains in balance during this loading, transporting, and unloading. The ability of a single operator to perform the rescue operation without assistance and the safety of the transported person while sitting backward are considered prerequisites. In the design concept subject to this article, an integrated seat is designed. This seat is connected to the motorcycle with a parallel link mechanism, which is lowered to the level where the patient can be easily seated by pulling a lever and can be fixed to the back of the motorcycle by pushing the same arm after the patient is loaded. One prototype was manufactured and integrated into a cargo scooter with an air-cooled 125 cc engine. Analysis and simulations were done, then road tests were successfully conducted using a full-size passenger mock-up, and then the collected data were analyzed. The test studies were carried out on platforms with a maximum slope of 14% and the maximum acceleration values were determined as 1.4 m/s(2) in acceleration and 2.7 m/s(2) in braking, and these values were found to be within the theoretical safe working area. Road performance tests confirmed compatibility with theoretical predictions for cornering speeds and side tilt angles, demonstrating the system's viability for real-world applications. This design offers a cost-effective solution for emergency transport in areas inaccessible to conventional ambulances, contributing significantly to disaster response and urban emergency care.
Keywords: Motorcycle ambulance; disaster relief; emergency response; transport of patients; TRANSPORT; SAFETY; DELAY; CARE; Engineering; Transportation